2008
DOI: 10.1111/j.1468-2435.2008.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Military Brides and Refugees: Vietnamese American Wives and Shifting Links to the Military, 1980 – 2000

Abstract: Since the immigration legislation of 1965, marriage to American citizens and resident aliens has been one of the primary paths for migration to the United States. Despite the rapid growth of the Asian American population over the course of the late twentieth century, Asian Americans had still reached only 3 per cent of all Americans by 2000, meaning that Asian marriage migration to the United States has been largely through marriage to non‐Asians. In this study, we look at exogamy among Vietnamese Americans us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The ACS 2008–2009 includes information obtained from spouses who can be paired to create couple‐level analysis. Data from other IPUMS samples have been used by other researchers to study intermarriages (e.g., Crowder & Tolnay, ; Hidalgo & Bankston, ) because the data include important demographic information on immigration, marriage, and other characteristics of immigrants.…”
Section: Methodsmentioning
confidence: 99%
“…The ACS 2008–2009 includes information obtained from spouses who can be paired to create couple‐level analysis. Data from other IPUMS samples have been used by other researchers to study intermarriages (e.g., Crowder & Tolnay, ; Hidalgo & Bankston, ) because the data include important demographic information on immigration, marriage, and other characteristics of immigrants.…”
Section: Methodsmentioning
confidence: 99%
“…This Act was extended to Laotians in 1976, paving the way for larger waves of Hmong and Laotian refugee arrivals in the years to follow. The Refugee Act of 1980 established policy for continued admission and settlement of refugees from Vietnam, Laos, and Cambodia throughout the United States; additionally, the Orderly Departure Program was created to assist Vietnamese relatives of refugees in leaving Vietnam or the camps in which they were located, and settling them in areas across the United States (Hidalgo & Bankston, 2008;Hing, 1997). Another wave of immigrants arrived following passage of the 1987 Amerasian Homecoming Act, which specifically allowed Vietnamese children of American soldiers from the war to enter the United States along with their immediate families.…”
Section: Southeast Asiansmentioning
confidence: 99%
“…Another wave of immigrants arrived following passage of the 1987 Amerasian Homecoming Act, which specifically allowed Vietnamese children of American soldiers from the war to enter the United States along with their immediate families. An estimated 83,000 immigrants had arrived in the United States by 1993 under this provision (Hidalgo & Bankston, 2008).…”
Section: Southeast Asiansmentioning
confidence: 99%
“…However, the rapidly rising size of the Asian American population raises the possibility that an increase in potential Asian marriage partners may result in decreasing exogamy, following the logic of the structural determinants of marriage choices discussed above. Hidalgo and Bankston (2008) found that the quick expansion of the Vietnamese American population from 1980 to 2000 was accompanied by a decrease in the rate of out-marriage, although they suggested that this was due to the decline in military brides in the decades following the Vietnam War as well as to the increasing numbers of Vietnamese Americans. In addition, perceptions of Asians as a single group by the larger American population may encourage interethnic associations, and therefore marriages, among people of different Asian groups.…”
Section: Asians and Out-marriagementioning
confidence: 99%